Status of Financial Inclusion in Rural India - Joshi, Umesh; Banerjee, Sudip (Journal of Advanced Research in English & Education, 2024)
India’s economy is among the fastest growing in the world and is estimated to be the fifth largest in terms of GDP in 2023. In India, many people are staying in rural villages. India’s rural economy is less developed compared to cities and urban areas. The economic conditions of rural people are poor when compared with urban areas. After demonetization at the end of 2016, it has been seen that more people participated in financial inclusion. India’s Reserve Bank and government have launched several projects to increase people’s awareness and participation in financial inclusion schemes. Indian Banking industry is the major player in implementing services for financial inclusion among Indians. This paper tries to find out rural India’s people’s awareness, acceptance, and participation in spreading awareness campaigns in rural areas of financial inclusion services and trying the figure out the people concern area in 2024. This study was conducted in Daudkhedi Village, Ujjain District of Madhya Pradesh.